Inbreeding reduces fitness in spatially structured populations of a threatened rattlesnake - Meaghan I. Clark; Eric T. Hileman; Jennifer A. Moore; Lisa J. Faust; Randall E. Junge; Brendan N. Reid; Danielle R. Bradke; Gideon S. Bradburd; Sarah W. Fitzpatrick (Proceedings of the National Academy of Sciences, 2025)
Small and fragmented populations are at high risk of local extinction, in part because of elevated inbreeding and subsequent inbreeding depression. A major conservation priority is to identify the mechanisms and extent of inbreeding depression in small populations. The eastern massasauga ( Sistrurus catenatus ) rattlesnake is listed as Federally Threatened in the United States, having experienced significant habitat fragmentation and concomitant population declines over the past 200 years. Here, we use long-term monitoring of two wild populations of eastern massasaugas in Michigan to estimate the extent of inbreeding in each population, identify mechanisms that generate inbreeding, and test for the impact of inbreeding on fitness. Using targeted genomic data and spatial coordinates of capture locations from over 1000 individuals, we find evidence of inbreeding and link inbreeding to spatial kinship structure within populations, possibly driven by limited dispersal. We reconstruct multigenerational pedigrees for each population to measure reproductive output and use long-term capture–recapture data to estimate individual survival (i.e., the two major components of fitness). We find evidence of inbreeding depression in both fitness metrics. The 5% most inbred individuals are 13.5% less likely to have any surviving offspring and have 11.6% lower annual survival compared to all less inbred individuals. By combining genomics and long-term monitoring data, we are able to link the life history of eastern massasaugas to inbreeding and detect relationships between fitness and inbreeding. These insights provide important conservation context for future management and for understanding how spatial structure can generate inbreeding depression even at fine spatial scales.